1998
DOI: 10.1046/j.1432-1327.1998.2560112.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification, characterization and complete amino acid sequence of nuclease Cl from Cunninghamella echinulata var. echinulata

Abstract: It is known, from the zymogram method of nuclease activity assay, that the crude extracts of Cunninghamella echinulata var. echinulata contained at least three distinct extracellular nucleases. Among them, the major form was 30 kDa in molecular mass and termed nuclease C1. In this report, nuclease C1 was purified to apparent homogeneity by chromatography on Cibacron blue-3GA, phenyl-Sepharose 4B and HiTrap Heparin. Nuclease C1 acquired enzymatic activity in the presence of Mn 2ϩ or Mg 2ϩ and was inhibited by E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 27 publications
(45 reference statements)
0
26
0
Order By: Relevance
“…RNA, ss, and dsDNA substrates (Friedhoff et al 1996;Ho et al 1998;Meiss et al 1998). Several nucleases of this family have either no or low RNase activity (Ho and Liao 1999;Wang et al 2000), but no differences between cleavage activity against ss and dsDNA have been noted to date.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA, ss, and dsDNA substrates (Friedhoff et al 1996;Ho et al 1998;Meiss et al 1998). Several nucleases of this family have either no or low RNase activity (Ho and Liao 1999;Wang et al 2000), but no differences between cleavage activity against ss and dsDNA have been noted to date.…”
Section: Discussionmentioning
confidence: 99%
“…RNase activity assay was measured essentially as described by Ho et al (1998). The reaction mixture (20 µL) contained 50 mM Tris-HCl (pH 8.0), 5 mM MgCl 2 , and 0.6 Kunitz units of DSN.…”
Section: Dsn Activity Analysismentioning
confidence: 99%
“…[26], Lysobacter enzymogens [27], Saccharomyces cerevisiae [30], Anabaena sp. PCC 7120 [33], Syncephalastrum racemosum [34], Cunninghamella echinulata [38], Streptomyces antibioticus [39] and Rhizopus stolonifer [40] are extracellular in nature. Endonucleases of mitochondrial origin have been reported from N. crassa [11,24], S. cerevisiae [28,29,31] and Aspergillus nidulans [32].…”
Section: Occurrence and Localizationmentioning
confidence: 99%
“…The presence of Mn 2+ and Mg 2+ was proved to be essential for both dsDNA and ssDNA hydrolyzing activity of C1 nuclease from Cunninghamella echinulata var. echinulata [18]. This observation indicated that the single stranded substrate hydrolyzing activity was highly favored in the presence of both Mn 2+ and Fe 2+ .…”
Section: Discussionmentioning
confidence: 82%